SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN PEMBERIAN MODAL USAHA DI PNM ULAMM SYARIAH SIGLI MENGGUNAKAN METODE WEIGHTED PRODUCT MODEL (WPM) BERBASIS WEB - Muhammad Daniel Fuat; Husaini; Zulfa Razi (Yayasan Sagita Akademia Maju, 2023)
This study discusses the problems that exist in the Sigli Syariah Ulamm PNM environment where the problem is providing a determination of the provision of venture capital in Pidie district. The distribution of capital assistance is one of the right solutions for reducing poverty and expanding employment. To design a Decision Support System for providing business capital assistance at PNM Ulamm Syariah Sigli using the Weighted product model (WPM) method, the decision-making method by multiplying to connect attribute rating, the rating of each attribute must first be raised to the weight of the attribute in question. A decision support system for the feasibility of providing venture capital at PNM Ulamm Syariah Sigli using the web-based weighted product model (WPM) method can help make it easier, to assess the verification customer data for providing business capital for Ulamm Syariah Sigli